Chronic hepatitis C patients prior to broad access to interferon-free treatments in Germany - Hüppe, D.; Buggisch, P.; Christensen, S.; Heiken, H.; Mauss, S.; Naumann, U.; Fischer, C.; Kleine, H.; Huelsenbeck, J. (Zeitschrift für Gastroenterologie, 2016)
In 2014, the first interferon-free treatment options for chronic Hepatitis C (CHC) became available in Europe introducing a new era of highly effective and well tolerated oral treatment options for CHC. The data from the cross-sectional study CURRENT-C highlights the epidemiological characteristics of patients with CHC in Germany. During the period that the study was conducted, the approval of the combination drugs for the treatment of CHC was imminent.Between June and November 2014, 1471 CHC-patients not receiving anti-HCV treatment were included nationwide in 40 German centers specializing in viral hepatitis. The mean age was 52.4 years with 41.2 % of the patients being female. Presumed route of infection in male patients was most frequently drug use (46.2 %) and blood products in females (22.8 %). The route of infection was unknown in 28.2 % of male and 43.1 % of female patients. Compared to male patients, female patients were older (55.6 vs. 50.1 years) and longer diagnosed with HCV (18 vs. 15 years). First language of the patients was most frequently German (72.2 %), followed by Russian (14.2 %), and Polish (2.9 %). HCV genotype (GT) 1 was found in 73.8 % (1a 29.0 %, 1b 38.4 %), GT2 in 3.5 %, GT3 in 18.3 %, GT4 in 4.2 %, GT5 in 0.2 %, and GT6 in 0.3 %. Liver cirrhosis was diagnosed in 15.7 % of the patients (17.1 % male, 13.7 % female). 43.2 % of the patients had already received HCV treatment, most frequently dual therapy with pegIFN + RBV (75.8 %) or triple therapy with telaprevir or boceprevir (20.3 %). Compared to treatment-naïve patients, pretreated HCV patients were older (55.1 vs. 50.3 years) and more frequently had liver cirrhosis as clinical diagnosis (22.2 % vs. 10.8 %). Patients scheduled for HCV treatment within the next 3 months had higher rates of pre-treatment (49.4 % vs. 37.0 %), and liver cirrhosis (21.4 % vs. 10.0 %).Compared to epidemiological data of Hüppe et al. 1 from 2003 to 2006, Klass et al. 2 stated in 2012 in a comparable setting that the German CHC population were older and had more advanced liver disease. The current data seem to support this ongoing trend towards more difficult to treat patients with an urgent need for new treatment options.
Keywords: Virushepatitis; Hepatitis C; Leber